Dendrobium species regulate energy homeostasis in neurodegenerative diseases: a review - Feixuan Wang; Jingqiong Wan; Yangzhen Liao; Shangyu Liu; Yuan Wei; Zhen Ouyang (Food Science and Human Wellness)
ABSTRACT: Brain energy homeostasis is a vital physiological function in maintaining a balanced internal metabolic environment. The impairment of energy homeostasis is recognized as a key pathophysiological basis for brain metabolic disorders and related neurodegenerative diseases. Dendrobium species ('Shihu' in Chinese) such as D. officinale, D. huoshanense, D. nobile, D. chrysanthum, D. loddigesii, D. moniliforme, D. gratiosissimum, D. candidum and D. caulis are widely used as traditional Chinese medicines/nutraceuticals to control and treat neurodegenerative disorders. These dietary herbs and their derived compounds possess a variety of biological properties, such as suppression of oxidative stress and neuroinflammation, regulation of energy homeostasis mainly through improving brain mitochondria function, insulin signaling and lipid metabolism. Furthermore, they reduce neurotoxicity, alleviate brain injury and neuropathy, and prevent neurodegenerative conditions including stroke, Alzheimer's disease, Parkinson's disease, and Huntington's disease in humans and/or rodents. Moreover, the nutraceuticals from Dendrobium species promote gut health and aid digestion, which appear to be associated with beneficial effects on brain energy homeostasis. Based on the above-mentioned health benefits associated with Dendrobium species, this work reviews their nutraceutical role in neurodegenerative disorders and further suggests the need to elucidate mechanisms of the underlying molecular actions.